2017
DOI: 10.1038/s41598-017-01061-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of CD146 in solid tumor: A Systematic Review and Meta-analysis

Abstract: CD146, also known as melanoma cell adhesion molecule, was initially identified as a marker of melanoma progression and metastasis. Recently many clinical studies investigated overexpression of CD146 predict poor prognosis of solid tumor, however, the results was inconclusive, partly due to small numbers of patients included. This present meta-analysis was therefore performed utilizing the results of all clinical studies concerned to determine the prognostic value of CD146 expression in solid tumors. Relevant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…In contrast to the above functions of METCAM/MUC18, recent work done on other solid tumors appears to be consistent with the meta-analysis results of solid tumors [53], as described next. For example, METCAM/MUC18 expression correlates with the epithelial-mesenchymal transition (EMT) markers and a poor prognosis in gastric cancer [57].…”
Section: Metcam/muc18: a Tumor Promoter In Most Solid Tumorssupporting
confidence: 83%
See 2 more Smart Citations
“…In contrast to the above functions of METCAM/MUC18, recent work done on other solid tumors appears to be consistent with the meta-analysis results of solid tumors [53], as described next. For example, METCAM/MUC18 expression correlates with the epithelial-mesenchymal transition (EMT) markers and a poor prognosis in gastric cancer [57].…”
Section: Metcam/muc18: a Tumor Promoter In Most Solid Tumorssupporting
confidence: 83%
“…However, its role in the development of most of these cancers is not well known. Recent meta-analysis suggests that high METCAM/MUC18 expression in many solid tumors appears to be associated with poor prognosis and patient survival [53]. However, in contrast to the conclusion, reduced expression of METCAM/MUC18 associates with the malignant progression of hemangioma [46].…”
Section: Colorectal Cancer Hemangioma and Pancreatic Cancermentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have reported that the highest expression of twist-1 was associated with high grade, invasion, metastases, and therefore unfavorable prognosis in different cancers as thyroid (28), and lung carcinomas (29). these results regarding twist-1 may help to find a new therapeutic target to inhibit the invasion, progression, and metastases in PC.…”
Section: Discussionmentioning
confidence: 88%
“…CD146 is a transmembrane glycoprotein belonging to the immunoglobulin superfamily; its increased expression is closely associated with an advanced stage of malignant melanoma, prostate and ovarian cancers (14). CD146 was tested on smear specimens of PEs from MPM and MH patients.…”
Section: Diagnostic Markers By Ihc or Fishmentioning
confidence: 99%